Relationship Between Blood Pressure Values and High-Density Lipoprotein (HDL) Levels in Hypertensive Patients at Balaraja Hospital - Novia Nur Andini; Nining Kurniati; Yuliani, Raden Adjeng Dewi Maria; Nadia Guntari; Priscila Santos (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2025)
Blood pressure and high-density lipoprotein (HDL) levels are two major indicators used in the assessment of cardiovascular health. Both play important roles in the risk of heart disease and stroke. High blood pressure, both systolic and diastolic, is a major risk factor for various cardiovascular diseases. Meanwhile, HDL levels are often considered